Internal and External Heat Balance Characteristic of Helicopter Intermediate Reducer Casing based on CFD - Wenbin Pan; Wenchang Ge; Chunlei Wang; Yongsheng Ai (Jixie chuandong)
Taking an intermediate reducer as the research object， the thermal-fluid coupling calculation model is established， and the boundary conditions of the external flow field of the intermediate reducer is set by using Fluent simulation technology， internal and external heat balance of the intermediate reducer are analyzed. The method of applying heat source inside the casing is simplified， and the effects of different air velocities on the pressure， convective heat transfer coefficient and temperature distribution of the casing wall are analyzed. The simulation results show the maximum pressure appears on the windward side of the casing under different air velocities， and the two end faces of the casing and the leeward side are in a negative pressure state， which is related to the inlet and outlet position of the external air flow field. The temperature of the windward side of the casing is lower than that of the leeward side. With the increase of air velocity， the heat dissipation performance of the casing is enhanced， but the wall pressure is also increasing. Therefore， the air velocity should be considered from the heat dissipation and strength of the casing.